Proper motion, spectra, and timing of PSR J1813–1749 using Chandra and NICER. Issue 3 (1st September 2020) - Ho, Wynn C G; Guillot, Sebastien; Saz Parkinson, P M; Limyansky, B; Ng, C-Y; Bejger, Michał; Espinoza, Cristóbal M; Haskell, B; Jaisawal, Gaurava K; Malacaria, C
ABSTRACT: PSR J1813–1749 is one of the most energetic rotation-powered pulsars known, producing a pulsar wind nebula (PWN) and gamma-ray and TeV emission, but whose spin period is only measurable in X-ray. We present analysis of two Chandra data sets that are separated by more than 10 yr and recent NICER data. The long baseline of the Chandra data allows us to derive a pulsar proper motion $\mu _{\rm RA}=(-0.067\pm 0.010)\, \mathrm{ arcsec}\, \mathrm{yr^{-1}}$ and $\mu _{\rm Dec.}=(-0.014\pm 0.007)\, \mathrm{ arcsec}\, \mathrm{yr^{-1}}$ and velocity $v_\perp \approx 900\!-\!1600\, \mathrm{km\, s^{-1}}$ (assuming a distance d  = 3–5 kpc), although we cannot exclude a contribution to the change in measured pulsar position due to a change in brightness structure of the PWN very near the pulsar. We model the PWN and pulsar spectra using an absorbed power law and obtain best-fitting absorption $N_{\rm H}=(13.1\pm 0.9)\times 10^{22}\, \mathrm{cm^{-2}}$, photon index Γ = 1.5 ± 0.1, and 0.3–10 keV luminosity $L_{\rm X}\approx 5.4\times 10^{34}\, \mathrm{erg\, s^{-1}}(d/\mbox{ 5 kpc})^2$ for the PWN and Γ = 1.2 ± 0.1 and $L_{\rm X}\approx 9.3\times 10^{33}\, \mathrm{erg\, s^{-1}}(d/\mbox{ 5 kpc})^2$ for PSR J1813–1749. These values do not change between the 2006 and 2016 observations. We use NICER observations from 2019 to obtain a timing model of PSR J1813–1749, with spin frequency ν = 22.35 Hz and spin frequency time derivative $\dot{\nu }=(-6.428\pm 0.003)\times 10^{-11}\, \mathrm{Hz\, s^{-1}}$ . We also fit ν measurements from 2009 to 2012 and our 2019 value and find a long-term spin-down rate $\dot{\nu }=(-6.3445\pm 0.0004)\times 10^{-11}\, \mathrm{Hz\, s^{-1}}$ . We speculate that the difference in spin-down rates is due to glitch activity or emission mode switching.